Influence of Various Irrigation Protocols on the Push-Out Bond Strength of TotalFill and AH Plus Bioceramic Sealers to Root Dentin: A Comparative In Vitro Study - Al Omari, Taher; Dkmak, Alaa; El-Farraj, Hamza; Albanna, Rami Haitham; Tabnjh, Abdelmalek K.; Atmeh, Amre R.; Aqrabawi, Jamal; Kim, Hyeon-Cheol; Song, Minju; Kwak, Sang Won (European Journal of Dentistry, 2025)
This study aimed to compare the push-out bond strength (POBS) of TotalFill (TFB) and AH Plus bioceramic (APB) sealers with different irrigation protocols.Sixty maxillary central incisors were prepared and randomly divided into three groups (n = 10) based on the final irrigation protocol. Group NC: 5.25% sodium hypochlorite (NaOCl); Group NE: 5.25% NaOCl and 17% EDTA; Group NH: 5.25% NaOCl and dual rinse HEDP (1-hydroxyethylidene-1,1-diphosphonic acid). Samples were obturated using either TFB or APB sealer only. In groups NC and NE, NaOCl was used during canal preparation, while in Group NH, NaOCl/HEDP was utilized. The teeth were then horizontally sectioned into three 3-mm thick sections at the apical, middle, and coronal levels. The POBS was performed on the root sections at a 1 mm/min speed. The failure mode was assessed using an optical microscope and a scanning electron microscope.Two-way ANOVA (analysis of variance) was used for statistical analysis to test the interaction between sealer type and irrigation solution, while an independent t-test was conducted to compare the means of the two sealer types at a significance level of 0.05.Specimens obturated with TFB showed significantly higher POBS than APB (p < 0.001). The highest bond strength was observed in the HEDP/TFB group and the lowest in the HEDP/APB group. Irrigation did not significantly influence the POBS (p > 0.05). Mixed failure was most commonly observed in all groups (>65%).TFB sealer had improved bond strength over APB sealer, regardless of the final irrigation protocol used, which did not significantly affect the bond strength.
Keywords: AH Plus bioceramic sealer; calcium silicate; HEDP; push-out bond strength; TotalFill